Asuhan Kebidanan Komunitas Pada Keluarga Tn “Z” di Dusun Bangkang Desa Prabu Wilayah Kerja Puskesmas Kuta - Rina Heri Wistuti; Hulfa Ahadian Haryanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The purpose of the study was to obtain a real picture in providing community midwifery care in the context of the family to Mrs. M with Postpartum and Neonatal Physiology in Bangkang Hamlet, Prabu Village, Pujut District, Central Lombok Regency. After practicing community midwifery and implementing comprehensive community midwifery care, a good working relationship with Mr. "Z"'s family was created, basic data assessment of Mr. "Z"'s family was conducted, data analysis was conducted on Mr. "Z"'s family data assessment, data analysis of Mr. "Z"'s family, formulation of problems in Mr. "Z"'s family, determining priority problems in Mr. "Z"'s family. Students have implemented a midwifery care action plan for Mr. "Z"'s family in the form of counseling. Students have been able to implement and evaluate midwifery care for Mr. "Z"'s family so that they can help change the habits of Mr. "Z"'s family for the better.